2011
DOI: 10.1210/me.2010-0277
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signaling 5 Is Highly Expressed in Parathyroid Tumors and Inhibits Signaling by the Calcium-Sensing Receptor

Abstract: The molecular mechanisms responsible for aberrant calcium signaling in parathyroid disease are poorly understood. The loss of appropriate calcium-responsive modulation of PTH secretion observed in parathyroid disease is commonly attributed to decreased expression of the calcium-sensing receptor (CaSR), a G protein-coupled receptor. However, CaSR expression is highly variable in parathyroid adenomas, and the lack of correlation between CaSR abundance and calcium-responsive PTH kinetics indicates that mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 27 publications
3
47
0
1
Order By: Relevance
“…46 RGS5 was reported to be markedly elevated in parathyroid adenomas, and mice deficient in RGS5 showed a reduced level of PTH plasma levels. 4648 Notably, forced expression of RGS5 in cells expressing CaSR abrogates the Ca 2+ -induced IP3 induction by CaSR. These results indicate that RGS5 can act as a physiological negative regulator of CaSR in the parathyroid gland.…”
Section: Rgs Proteins In Osteoblastsmentioning
confidence: 99%
“…46 RGS5 was reported to be markedly elevated in parathyroid adenomas, and mice deficient in RGS5 showed a reduced level of PTH plasma levels. 4648 Notably, forced expression of RGS5 in cells expressing CaSR abrogates the Ca 2+ -induced IP3 induction by CaSR. These results indicate that RGS5 can act as a physiological negative regulator of CaSR in the parathyroid gland.…”
Section: Rgs Proteins In Osteoblastsmentioning
confidence: 99%
“…Koh et al . (74) found that RGS5 is selectively up-regulated in parathyroid adenomas relative to normal glands. Transient expression of RGS5 in cells stably expressing CaR results in dose-dependent abrogation of calcium-stimulated inositol trisphosphate production and ERK1/2 phosphorylation.…”
Section: Rgs Proteins In the Regulation Of Signaling Pathwaysmentioning
confidence: 99%
“…An abnormal calcium-PTH set point has been well-described in aggregate dispersed cells from parathyroid adenomas, and most reports attribute the impaired set point in these cells to decreased expression of the calciumsensing receptor (CASR) (14,15) or more recently to altered expression of downstream molecules linked to CASR signaling, including RhoGEF and RGS5 (16,17). In contrast to clonal expansion following genomic tumor-initiating events, attenuated calcium responsiveness could be expected to drive polyclonal proliferation in the parathyroid gland.…”
mentioning
confidence: 99%